Back pain outcomes in primary care following a practice improvement intervention:- a prospective cohort study - Breen, Alan C (BioMed Central, 2011)
BACKGROUND: Back pain is one of the UK's costliest and least understood health problems, whose prevalence still seems to be increasing. Educational interventions for general practitioners on back pain appear to have had little impact on practice, but these did not include quality improvement learning, involve patients in the learning, record costs or document practice activities as well as patient outcomes. METHODS: We assessed the outcome of providing information about quality improvement techniques and evidence-based practice for back pain using the Clinical Value Compass. This included clinical outcomes (Roland and Morris Disability Questionnaire), functional outcomes, costs of care and patient satisfaction. We provided workshops which used an action learning approach and collected before and after data on routine practice activity from practice electronic databases. In parallel, we studied outcomes in a separate cohort of patients with acute and sub-acute non-specific back pain recruited from the same practices over the same time period. Patient data were analysed as a prospective, split-cohort study with assessments at baseline and eight weeks following the first consultation. RESULTS: Data for 1014 patients were recorded in the practice database study, and 101 patients in the prospective cohort study. We found that practice activities, costs and patient outcomes changed little after the intervention. However, the intervention was associated with a small, but statistically significant reduction in disability in female patients. Additionally, baseline disability, downheartedness, self-rated health and leg pain had small but statistically significant effects (p < 0.05) on follow-up disability scores in some subgroups. CONCLUSIONS: GP education for back pain that both includes health improvement methodologies and involves patients may yield additional benefits for some patients without large changes in patterns of practice activity. The effects in this study were small and limited and the reasons for them remain obscure. However, such is the impact of back pain and its frequency of consultation in general practice that this kind of improvement methodology deserves further consideration. TRIAL REGISTRATION NUMBER: ISRCTN: ISRCTN30420389